A Study On The Relationship Between Job Design and Innovative Work Behavior - WAHAB, ETA (Research in Management of Technology and Business, 2022)
Job design is essential to reduce and overcome job dissatisfaction arising from repetitive tasks. Innovative work behavior is considered as one method in solving employee problem by crafting new idea. This study has been conducted because less studies on how job design could affect innovation in service sector had been conducted in Malaysia. Thus, this study attempts to identify the relationship between job design and Innovative Work Behavior (IWB). The objectives of this research are to determine the level of job design among employees in service sector, to determine the level of IWB among employees in service sector and to address the relationship between job design and IWB. Quantitative study had been used in this study. An online survey has been conducted among 234 employees in service sector in Ampang, Selangor with a response rate of 67.8%. Data were evaluated using descriptive analysis and Spearman’s correlation analysis. This study found that the level of job design and innovative work behavior is moderate. Only skill variety, task significance and autonomy had a substantial relationship with innovative work behavior.